Retrograde intramedullary headless compression screws for treatment of extra-articular thumb metacarpal base fractures. (July 2020) - Barrera-Ochoa, Sergi; Alabau-Rodriguez, Sergi; Campillo-Recio, David; Esteban-Feliu, Ignacio; Mir-Bullo, Xavier; Soldado, Francisco
The purpose of the study was to evaluate clinical and radiological outcomes of extra-articular fractures involving the base of the thumb metacarpal treated with fixation using a retrograde intramedullary cannulated headless screw. A review of prospectively collected data was conducted on a consecutive series of 13 patients, treated with headless screw fixation for acute displaced fractures. All workers resumed full duties, while non-workers returned to unlimited leisure activities within a mean of 42 days. At 3 months follow-up, all range of motion measurements in the treated and untreated thumb were similar. Mean visual analogue pain score was 0.8 at rest and 1.4 during exercise and mean Quick Disabilities of the Arm, Shoulder, and Hand score was 5. All patients achieved radiographic union by 8 weeks. We conclude that the intramedullary headless screw fixation is safe and reliable for base of thumb metacarpal fractures, allowing for early postoperative motion and good functional recovery. Level of evidence: IV